Multiple effects of the PHO91 gene knockout in Ogataea parapolymorpha - Farofonova, Vasilina; Andreeva, Nadeshda; Kulakovskaya, Ekaterina; Karginov, Azamat; Agaphonov, Michael; Kulakovskaya, Tatiana (Folia microbiologica, 2023)
Pho91 is a vacuolar phosphate transporter that exports phosphate from the vacuolar lumen to the cytosol in yeast cells. In this study, we have demonstrated the pleiotropic effects of the PHO91 gene knockout in the methylotrophic yeast Ogataea parapolymorpha (Hansenula polymorpha, Ogataea angusta). The content of both acid-soluble and acid-insoluble inorganic polyphosphate (polyP) in the ∆pho91 cells was slightly higher compared to the strain with wild-type PHO91, when the cells were cultivated on glucose. The pho91-Δ mutations both in O. parapolymorpha and in Saccharomyces cerevisiae diminished resistance to cadmium and increased resistance to manganese and peroxide stresses. The cells of the mutant strain of O. parapolymorpha were unable to consume methanol due to the lack of methanol oxidase activity. We speculate that these effects are associated with the inability of mutant cells to mobilize phosphate from the vacuolar pool and/or defects in the signaling pathways involving phosphate, polyP, and inositol polyphosphates.
Keywords: Ogataea parapolymorpha; Polyphosphate; Heavy metal stress; Saccharomycetales; Methanol oxidase; PHO91; Methanol consumption; genový knockout; Gene Knockout Techniques; Polyphosphates; Pleiotropic effect; polyfosfáty